Organization, structure and information technology - Zaliwski A. (Selected readings on economies in transition, 2000)
This paper gives a brief review of the different aspects of strategic use of information technology and emerging organizational structures, especially in the service context. The dynamically changing situation and new organizational forms (virtual or network corporations) reveals new challenges for managers and IS analysts. They should reply with radical organizational changes and strategic IT applications. The combined effect of the organizational changes with IT can reshape a firm's strategic position to give it a sustained competitive advantage. This is especially important for countries undergoing economic transformation, like Poland. In the case of Poland, an introduction of strategic IT applications was inherited after years of ruling under a socialist economy.